Assessment of the maximal aerobic speed in young elite soccer players: Université de Montréal Track Test (UM-TT) vs. treadmill test - Los Arcos, A.; Vázquez, J. S.; Villagra, F.; Martin, J.; Lerga, J.; Sánchez, F.; Bertó, J.; Zulueta, J. J. (Science & Sports, 2019)
Objective: The main aim of this study was to examine the association between the Maximal Aerobic Speed (MAS) measured by the Université de Montréal Track Test (UM-TT) and on a running treadmill test in young elite soccer players. Equipment and methods: Fourteen U-16 male soccer players (mean±SD: age=15.5±0.7 years; height=1.76±0.5m; weight=67.7±4.5kg) from a Spanish First Division club academy participated in the study. The participants were submitted to the Université de Montréal Track Test (UM-TT) and an intermittent treadmill test with a one-week interval. Results: The MASs, the speed at the last completed stage (16.6±0.8 kmh-1) and calculated using the formula of Kuipers et al. (17.2±0.7 kmh-1), were substantially higher (Effect size>0.8) than that measured on the treadmill (15.9±0.9 kmh-1). The MAS measured by the UM-TT correlated highly (r>0.6) with the MAS measured on the treadmill. Conclusion: Despite the large association between both values, the MAS measured by the UM-TT differs considerably from the MAS measured on a running treadmill in young elite soccer players. It suggests that, in soccer training, caution should be applied when using the velocity of the MAS measured on the UM-TT or in a laboratory interchangeably.